1979
DOI: 10.1346/ccmn.1979.0270207
|View full text |Cite
|
Sign up to set email alerts
|

High Surface Area Solids Obtained by Reaction of Montmorillonite with Zirconyl Chloride

Abstract: Abstract--Exchange reactions of Na-montmorillonite with zirconyl chloride solutions give products with basal spacings near 18 A which are stable to 500~ and have surface areas of the order of 300-400 m2/g. The Na ions are exchanged with tetrameric hydroxy cations [Zr4(OH)I( nH~O] 2+. The high surface area is attributed to the porosity formed by stable zirconium oxide" pillars" formed by dehydroxylatlon of the complex cation. The nitrogen adsorption isotherms are of Langmuir type and are consistent with adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(75 citation statements)
references
References 8 publications
3
72
0
Order By: Relevance
“…It is also reported that inter-layer distance is almost perfectly maintained even at 500°C, showing that thermal stability is also good. Yamanaka et al [30] created zirconia pillars between montmorillonite layers and obtained an inter-layer compound with an inter-layer distance of 0.84 nm and a specific surface area of about 500 m 2 /g. Also reported is a bridge formation method that selectively deposits metal hydroxides only between clay mineral layers, without using ion exchange.…”
Section: Synthesizing Atom and Molecule Porementioning
confidence: 99%
“…It is also reported that inter-layer distance is almost perfectly maintained even at 500°C, showing that thermal stability is also good. Yamanaka et al [30] created zirconia pillars between montmorillonite layers and obtained an inter-layer compound with an inter-layer distance of 0.84 nm and a specific surface area of about 500 m 2 /g. Also reported is a bridge formation method that selectively deposits metal hydroxides only between clay mineral layers, without using ion exchange.…”
Section: Synthesizing Atom and Molecule Porementioning
confidence: 99%
“…This type of Na-bentonite was studied by Yamanaka and Brindley (1979) and Vaughan and Lussier (1980). The chemical composition (Table 1) provided by the supplier is typical of this material.…”
Section: Montmorillonitementioning
confidence: 99%
“…In fact, Yamanaka and Brindley (1979) reported that by exchange reactions with tetrameric hydroxy cations, [(Zr4(OH)14" nH20)] +2, Na-montmorillonites with surface areas as high as 300-400 mZ/g, stable to 500~ can be obtained. Similarly, Vaughan et al (1979) noted that …”
Section: Surface Area and Surface Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Various sizes of inorganic polyhydroxocations have been intercalated as pillaring precursors to control the pore size. [1][2][3] Silica is one of the oxides of interest for obtaining thermally stable and catalytically active pillared clays. Silica pillared clays have been prepared from a titania-silica or iron oxide-silica complex sol because silica precursors are silicate anions, which cannot enter between the clay sheets.…”
Section: Introductionmentioning
confidence: 99%